Dithiol‐Activated Bioorthogonal Chemistry for Endoplasmic Reticulum‐Targeted Synergistic Chemophototherapy. Issue 52 (24th November 2022) - Sun, Jian; Zhang, Xiaoran; Wang, Xia; Peng, Jinlei; Song, Gang; Di, Yufei; Feng, Fude; Wang, Shu
Abstract: The controlled intracellular release of nitrite is still an unmet challenge due to the lack of bio‐friendly donors, and the antitumor effect of nitrite is limited by its physiologically inert activity. Herein, we designed benzothiadiazole‐based organic nitrite donors that are stable against bio‐relevant species but selectively respond to dithiol species through SN Ar/intramolecular cyclization tandem reactions in the aqueous media. The bioorthogonal system was established to target the endoplasmic reticulum (ER) of liver cancer HepG2 cells. The nitrite and nonivamide were coupled to induce elevation of intracellular levels of calcium ions as well as reactive oxygen/nitrogen species, which resulted in ER stress and mitochondrial dysfunction. We demonstrated that a combination of photoactivation and "click to release" strategy could enhance antitumor effect in cellular level and show good potential for cancer precision therapy. Abstract : Bioorthogonal chemistry is introduced for design of organic nitrite donors, on the basis of SN Ar and cyclization reactions between dithiols and 5‐nitrobenzo[c][2, 1, 3]thiadiazole derivatives. A combination of "click to release" strategy and photoactivation is achievable for cancer chemophototherapy.